Successful Treatment of Pseudoaneurysm Following Left Distal Transradial Cardiac Catheterization With Compression Device. Issue 2 (June 2019) - Prejean, Shane P.; Von Mering, Gregory; Ahmed, Mustafa
Distal transradial artery access has emerged as a promising new method of access for coronary and endovascular procedures. With the increasing use of distal transradial artery access, operators will need to gain experience in the management of complications in the anatomical snuffbox. We review the rationale behind distal transradial access and summarize rate of vascular complications, based on the review of the literature. We then report a case of pseudoaneurysm in the distal left radial artery occurring 20 hours after cardiac catheterization likely precipitated by intravenous heparin and dual antiplatelet therapy with aspirin and prasugrel received during a second procedure. A modified compression technique with the TR band® (Terumo Medical Corporation, Tokyo, Japan) was used in which the rigid, plastic insert was removed prior to application to facilitate improved apposition of the band on the dorsum of the hand, and waveforms from continuous pulse oximetry were used to guide "patent compression." Thrombosis of the pseudoaneurysm was achieved in 12 hours, and no further intervention was required.